Hubungan Pemenuhan Informasi Pasien Pre Operasi Dengan Tingkat Kecemasan Di Rumah Sakit XX Palembang - Zuhrah Gia Tamah; Muliyadi Muliyadi; Sri Yulia (Universitas Muhammadiyah Surakarta, 2019)
Background: Surgery is medication of invasive technique causing physical trauma and risk of death. This high risk can cause a psychological effect namely anxiety in the form of recovery process duration after a surgery.A patient that will go through a surgery feels anxious and needs an intervention of information fulfillment. Objective of the Study: This study aimed to find out the relationship between information fulfillment of pre-surgery patients and their level of anxiety at Muhammadyah Hospital of Palembang in 2017. Method: This study was quantitative using an analytical descriptive design with cross- sectional approach. The sampling technique was accidental sampling with the number of samples of 35 respondents. The data were collected using questionnaire with 12 items of information fulfillment statements and 20 items of statements of anxiety level. This study used bivariate analysis with chi square test. Results: The patients having poor information fulfillment were 22 respondents (62.9%), while those feeling anxious were 23 respondents (65.7%). The results of the statistical test showed that there was a relationship between information fulfillment and level of anxiety (p value = 0.024). Conclusion and Suggestion: Information fulfillment is very important to be carried out to decrease the anxiety of pre-surgery patients. It is expected that health workers particularly nursesapply their knowledge and formulate how to decrease the anxiety of the patients facing a surgery and information standard of pre-surgery condition that can be provided by the nurses in the form of pre-surgery nursing care.